By a blazing blue sea - Garne, S. T.; Lohstoeter, Lori (San Diego : Harcourt Brace, 1999)
A rhyming description of the simple and colorful life of a Caribbean fisherman.
"Gulliver books"
2.9
K-3
K-3
School Library Journal
Booklist
Keywords: Color -- Fiction; Stories in rhyme; Color -- Fiction; Stories in rhyme; Caribbean Area -- Juvenile fiction; Caribbean Area -- Fiction; Caribbean Area -- Fiction